Development of pepper nozzle seedling with different fertilization - Pagliarini, Maximiliano Kawahata; Castilho, Regina Maria Monteiro de; Mariano, Flávia Aparecida de Carvalho (Ornamental Horticulture, 2014)
The objective of this work was to test the slow and conventional release fertilization on pepper nozzle initial seedling development. It was developed at UNESP, Campus of Ilha Solteira-SP, in Pad & Fan greenhouse, from 9th October to 18th November 2010, with seedlings produced at UNESP in plastic tray with 60 cells filled with commercial substrate, when it was 4 or 6 leaves they were transplanted in plastic vases with 1.3 L of volume filled with commercial substrate. It was chosen completely randomized design with four treatments and twenty repetitions. The treatments were: T1 = control (without fertilization), T2 = slow release fertilization Osmocote 3M (15-09-12), T3 = slow release fertilization Basacote 3M (16-08-12) and T4 = total release fertilization (04-30-10), everyone with 3 g L-1 substrate. The parameters analyzed were: plant height, steam diameter, chlorophyll content and number of flowers and fruit. The slow release fertilization were more efficient than convention one for the study variable.